Improve Capsicum spp. Seed Quality in Seedling Using Microorganism Organic Fertilizers - Juhariah, Jujuk; Lestariana, Dwi Suci; Aulia, Margaretha Praba (METANA, 2020)
This study aims to improve the seed quality in seedling using microorganism-based fertilizer. This study was conducted from July to September 2019 at Boyolali Universityâ€™s greenhouse. This experiment was an arranged factorial randomized block design with three factors, which are three chili varieties (green, white, and curly chili) and three kinds of organic fertilizers (microalgae, effective microorganisms, and local microorganisms). Then the plants observed five times. Parameters observed are the living plant number, leavesâ€™ number, and plant height. The results show that there was no significant difference in living plant numbers among all the treatments. The significant differences appear in the number of leaves and plant height. The significant difference indicated that the difference influenced by the plant type not because of the application of the fertilizer.Â